NATURAL RESOURCES AND THEIR CONSERVATION: प्राकृतिक संसाधन एवं उनका संरक्षण - Singh, Anita; Singh, Ragini (International Journal of Research -GRANTHAALAYAH, 2015)
Nature has provided all the useful resources to man with free hand. Adivana relied entirely on nature to fulfill all its needs, but in the development of Adivasi from human to modern man, man exploited the natural resources in full and consequently the abundant wealth of nature gradually started to end. In this sequence, various species have reached the category of extinct species, conservation of natural resources has become imperative to preserve the remaining species and the human species itself. Along with taking various protective measures for this, the need is for the youth who are sensitive to nature and able to bear the responsibility of conservation of natural resources by staying in the nature of nature even in odd circumstances. प्रकृति ने मनुष्य को सभी जीवनोपयोगी संसाधन मुक्त हस्त से प्रदान किये हैं। आदिमानव अपनी समस्त आवष्यकताओं की पूर्ति के लिये पूरी तरह प्रकृति पर निर्भर करता था, किंतु आदि मानव से आधुनिक मनुष्य बनने की विकासयात्रा में मनुष्य ने प्राकृतिक संसाधनों का भरपूर दोहन किया फलस्वरूप प्रकृति की अकूत संपदा धीरे-धीरे समाप्त होने लगी। इस क्रम में विभिन्न प्रजातियाँ विलुप्त प्रजातियों की श्रेणी में पहुँच गयीं, शेष बची हुई प्रजातियों और स्वयं मनुष्य प्रजाति को बचाये रखने के लिये भी प्राकृतिक संसाधनों का संरक्षण अत्यावष्यक हो गया है। इस हेतु विभिन्न सुरक्षात्मक कदम उठाने के साथ-साथ आवष्यकता ऐसे युवाओं की है जो प्रकृति के प्रति संवेदनषील हों तथा विषम परिस्थितियों में भी प्रकृति के सानिध्य में रहकर प्राकृतिक संसाधनों के संरक्षण का उत्तरदायित्व निभाने में सक्षम हों।